Features Of The Course Of Infective Endocarditis In Children - Rasulov Rasul Akromjon ogli; Rakhmonov Farkhod Kholbayevich; Bakhriyev Ilyos Salohiddinovich (Academia One Publishing, 2026)
Infective endocarditis (IE) is a relatively rare but severe cardiovascular disease in children, characterized by a complicated clinical course and a high risk of systemic complications. This scientific study analyzes the etiological factors, clinical manifestations, diagnostic features, and specific characteristics of primary and secondary forms of infective endocarditis in pediatric patients. The research was conducted on the basis of clinical data obtained from 40 children and adolescents diagnosed with primary and secondary infective endocarditis who were treated at the clinics of the Tashkent Pediatric Medical Institute during 2021–2022. Based on clinical, laboratory, and paraclinical examinations, the acute and subacute forms of infective endocarditis, functional changes in the cardiovascular system, and immunological complications were evaluated. The results demonstrated that infective endocarditis in children most frequently develops against the background of congenital and acquired heart defects, and the disease course is predominantly subacute in the majority of cases.
Keywords: infective endocarditis; children; ECG; echocardiography